The Dynamic of Heterosexual Transmission of HIV-AIDS Model with Treatment - K. A. Bashiru; T. A. Ojurongbe; M. Lawal (Fountain Journal of Natural and Applied Sciences (FUJNAS), 2017)
A Mathematical Model of HIV/AIDS with Heterosexual transmission in the presence of treatment was examine in this paper, it ascertained the impact of treated individuals on the transmission dynamics of HIV/AIDS. Equilibrium points of the model system were found, stability analysis and numerical simulation were carried out, it was discovered that HIV/AIDS can die out with test of time as Ro < 1 . It was observed that the model had a disease free equilibrium which was asymptotically stable for Ro < 1 and unstable for Ro > 1. Graphical representations of the numerical analysis showing the effect of treatment on the model were also presented.